Hemodiafiltration Treatment for Severe Valproic Acid Intoxication: Case Report and Updated Systematic Literature Review - Tichelbäcker, Tobias; Herath, Judith; Tampe, Björn; Korsten, Peter (Frontiers in Medicine, 2018)
Background: Valproic acid (VPA) has been approved for the treatment of seizure disorders. It is also commonly used in psychiatric disorders, such as schizophrenia spectrum disorders. With increasing administration, reports of intoxications are more frequently reported. The most common findings of VPA intoxication are central nervous system depression, respiratory depression, hypotension, metabolic acidosis, and elevated lactate, among others. Methods: We describe a case report of VPA intoxication with hemodiafiltration (HDF) as extracorporeal treatment (ECTR) for removal of VPA. This treatment modality has only rarely been reported in the current literature. In addition, we performed an updated systematic literature review (SLR) of additional cases on the topic ranging from December 1st, 2014 to April 20th, 2018. We searched MEDLINE and Web of Science for relevant references. Results: In the presented case, VPA intoxication occurred in a 46-year-old female patient after oral ingestion of 56 g of VPA. In addition to vasopressors and endotracheal intubation, we administered L-Carnitine (L-Car) and performed hemodiafiltration treatment. After intravenous therapy with L-Car and simultaneous HDF sessions, we observed full recovery without neurological sequelae. The SLR identified 8 additional articles reporting favorable outcomes with extracorporeal treatments in most cases. Conclusion: HDF and other extracorporeal procedures are safe and effective therapeutic options in patients with VPA intoxication. The choice of ECTR modality mainly depends on local experience and the setting. In the present case, ingestion of 56 g was successfully treated with HDF. These findings are in line with several other case reports describing positive outcomes. Extracorporeal treatment, including HDF, should be considered early in the management of VPA intoxication. Supporting evidence is emerging, but it is of limited quality.